2023
DOI: 10.1038/s41598-022-26932-2
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the active knee joint position sense test and influence of limb dominance and sex

Abstract: The output of a sensorimotor performance can be measured with the joint position sense (JPS) test. However, investigations of leg dominance, sex and quality measures on this test are limited. Therefore, these potential influencing factors as well as reliability and consistency measures were evaluated for angular reproduction performance and neuromuscular activity during the active knee JPS test in healthy participants. Twenty healthy participants (10 males; 10 females; age 29 ± 8 years; height 165 ± 39 cm; bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…They found that center of pressure variability under the feet soles was equivalent between the right and left legs. Further investigation corroborated equivalent balance stability between the legs in quiet standing 7 , in addition to interlateral symmetric Special issue: "Fatigue issue in the performance of motor skills" coordinative structure 8 and muscular activation 9 . Similar findings of symmetric balance control between the legs has been observed also in more challenging conditions of unstable support base 10 , dynamic balance 11 , and in response to balance perturbations 12 .…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…They found that center of pressure variability under the feet soles was equivalent between the right and left legs. Further investigation corroborated equivalent balance stability between the legs in quiet standing 7 , in addition to interlateral symmetric Special issue: "Fatigue issue in the performance of motor skills" coordinative structure 8 and muscular activation 9 . Similar findings of symmetric balance control between the legs has been observed also in more challenging conditions of unstable support base 10 , dynamic balance 11 , and in response to balance perturbations 12 .…”
Section: Introductionmentioning
confidence: 69%
“…Closely related to the muscular responses required in our experiment, Vieira et al 12 showed that reactive responses in unipedal stance were symmetric between the legs in onset delay for muscular activation following a sudden stance perturbation 33 . Previous comparisons between the legs in the performance of tasks with different levels of difficulty failed to show asymmetries in balance stability 10 and in lower leg muscular responses 9,34 . Results of symmetric muscular responses between the legs are congruent with findings of bilateral activation of the primary sensory and motor areas 35,36 and dorsolateral prefrontal cortices 37 during feet-in-place reactive responses to balance perturbations.…”
Section: Symmetric Responses Between the Dominant And Non-dominant Legsmentioning
confidence: 84%
“…So standard differences in means were used to pool data. But the accuracy and reliability of various tools are different in examining the knee repositioning sense [ 38 40 ]. On the other hand, various exercise protocols were prescribed in eligible studies.…”
Section: Discussionmentioning
confidence: 99%